Impact of cholesterol on proinflammatory monocyte production by the bone marrow. (3rd August 2021) - Stiekema, Lotte C A; Willemsen, Lisa; Kaiser, Yannick; Prange, Koen H M; Wareham, Nicholas J; Boekholdt, S Matthijs; Kuijk, Carlijn; de Winther, Menno P J; Voermans, Carlijn; Nahrendorf, Matthias; Stroes, Erik S G; Kroon, Jeffrey
Abstract: Aim: Preclinical work indicates that low-density lipoprotein cholesterol (LDL-C) not only drives atherosclerosis by directing the innate immune response at plaque level but also augments proinflammatory monocyte production in the bone marrow (BM) compartment. In this study, we aim to unravel the impact of LDL-C on monocyte production in the BM compartment in human subjects. Methods and results: A multivariable linear regression analysis in 12 304 individuals of the EPIC-Norfolk prospective population study showed that LDL-C is associated with monocyte percentage (β = 0.131 [95% CI: 0.036–0.225]; P = 0.007), at the expense of granulocytes (β = −0.876 [95% CI: −1.046 to −0.705]; P < 0.001). Next, we investigated whether altered haematopoiesis could explain this monocytic skewing by characterizing CD34 + BM haematopoietic stem and progenitor cells (HSPCs) of patients with familial hypercholesterolaemia (FH) and healthy normocholesterolaemic controls. The HSPC transcriptomic profile of untreated FH patients showed increased gene expression in pathways involved in HSPC migration and, in agreement with our epidemiological findings, myelomonocytic skewing. Twelve weeks of cholesterol-lowering treatment reverted the myelomonocytic skewing, but transcriptomic enrichment of monocyte-associated inflammatory and migratory pathways persisted in HSPCs post-treatment. Lastly, we link hypercholesterolaemia to perturbed lipid homeostasis in HSPCs, characterized by lipid droplet formation and transcriptomic changes compatible with increased intracellular cholesterol availability. Conclusions: Collectively, these data highlight that LDL-C impacts haematopoiesis, promoting both the number and the proinflammatory activation of circulating monocytes. Furthermore, this study reveals a potential contributory role of HSPC transcriptomic reprogramming to residual inflammatory risk in FH patients despite cholesterol-lowering therapy. Graphical Abstract: